2018
DOI: 10.17235/reed.2018.5509/2018
|View full text |Cite
|
Sign up to set email alerts
|

Screening-detected colorectal cancers show better long-term survival compared with stage-matched symptomatic cancers

Abstract: patients with stage I and III tumors that were diagnosed via a screening program have a higher overall and disease-free survival at five and ten years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…Cienfuegos et al also reported that symptom‐detected CRC patients had nearly a 3‐fold higher risk of death compared to screening‐detected CRC patients. Improved 5‐year survival in the group screened by colonoscopy was observed in patients with stage I (HR, 4.03; 95% CI, 1.24‐13.07) and III (HR, 2.14; 95% CI, 1.09‐4.19) cancer 21 . Those HRs were higher than that observed in our study, which may be related to the screening modality.…”
Section: Discussioncontrasting
confidence: 76%
“…Cienfuegos et al also reported that symptom‐detected CRC patients had nearly a 3‐fold higher risk of death compared to screening‐detected CRC patients. Improved 5‐year survival in the group screened by colonoscopy was observed in patients with stage I (HR, 4.03; 95% CI, 1.24‐13.07) and III (HR, 2.14; 95% CI, 1.09‐4.19) cancer 21 . Those HRs were higher than that observed in our study, which may be related to the screening modality.…”
Section: Discussioncontrasting
confidence: 76%
“…This study revealed that, after adjusting for cancer stage and other variables, the mortality risks for colorectal cancer patients are ranked as follows: FIT-positive patients with follow-up examinations have the lowest risk, followed by FITpositive patients without follow-up, then FIT-negative patients, and finally, patients who were never screened have the highest risk. Unlike previous studies that compared prognoses between only two categories of patients-either screendetected versus symptomatically-diagnosed [11][12][13] or ever-screened versus never-screened 14 our research offers a more detailed stratification of patients' mortality risks. Specifically, we observed that patients who underwent screening, irrespective of their FIT results, consistently demonstrated lower mortality risks compared to those who were never screened.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have compared two types of colorectal cancer cases considering stage matching: the "screendetected" cases identified through screening methods and the "symptomatically diagnosed" cases detected based on the appearance of symptoms. [11][12][13] The research findings indicate that individuals who underwent colorectal cancer screening using methods such as colonoscopy or the traditional fecal occult blood testing (FOBT), also known as guaiacbased FOBT, showed significant survival advantages when diagnosed at more advanced stages. [11][12][13] However, discrepancies have arisen in their findings concerning early-stage colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,32] However, overall survival at 48 months was 84.2%, higher than that reported in other studies. [4,33,34] As regards anatomic pathology, 98.27% of the tumours showed histology compatible with adenocarcinoma, and only one with lymphoma.…”
Section: Discussionmentioning
confidence: 99%